OPTIMALISASI PENJUALAN UMKM BUNDO KANDUNG MELALUI PELATIHAN DIGITAL MARKETING - Jarti, Nanda; Putri , Weni Lestari; Sari , Chinta Yolanda (ASOSIASI IDEBAHASA KEPRI, 2025)
This community service activity aims to increase the capacity of Micro, Small, and Medium Enterprises (MSMEs) in the Bundo Kandung Community, Tiban Lama, in utilizing digital marketing as a strategy to increase sales and competitiveness in the digital era. Problems faced by MSMEs in this community include low understanding and skills in digital marketing, minimal use of social media and e-commerce, and limitations in creating attractive promotional content. Through digital marketing training covering basic branding materials, social media strategies, digital content creation, and the use of marketplace platforms, this activity is expected to provide practical and applicable understanding to participants. The implementation method includes interactive material delivery, direct practice, and technical assistance. The results of this activity show an increase in participants' knowledge and skills in marketing products digitally, as well as the emergence of a collaborative spirit among MSMEs to increase the competitiveness of local products online.